2008
DOI: 10.1007/s10452-008-9203-x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between prevalence of trematode parasite Diplostomum sp. and population density of its snail host Lymnaea stagnalis in lakes and ponds in Finland

Abstract: Diplostomum sp. is a trematode parasite that infects aquatic snails, e.g. Lymnaea stagnalis (Gastropoda: Lymnaeidae), fish, and fish-eating birds. Ponds and lakes (n = 28) located in Finland between latitudes 61°45 0 N and 65°30 0 N were sampled for L. stagnalis, the first intermediate host for Diplostomum sp. L. stagnalis were found in 22 sites out of 28, and Diplostomum sp. in 10 of the 22 snail populations. Among the L. stagnalis populations that were infected by Diplostomum sp., the mean prevalence was 12.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The lack of responses in the group of snails injected with trematode-infected gonad tissue is unexpected because a strong immune response could be assumed against trematode parasites as they are highly virulent (e.g. Karvonen et al, 2004) and also common in natural snail populations (Väyrynen et al, 2000;Voutilainen et al, 2009). However, it is possible that responses are simply not seen in the parameters measured in this experiment if some other defence mechanisms are used against them.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of responses in the group of snails injected with trematode-infected gonad tissue is unexpected because a strong immune response could be assumed against trematode parasites as they are highly virulent (e.g. Karvonen et al, 2004) and also common in natural snail populations (Väyrynen et al, 2000;Voutilainen et al, 2009). However, it is possible that responses are simply not seen in the parameters measured in this experiment if some other defence mechanisms are used against them.…”
Section: Discussionmentioning
confidence: 99%
“…This is possible due to both the biological characteristics of the species (large body size and biomass) and its ecological features (tolerance to water pollution and oxygen deficits) (Dudgeon and Morton, 1983;Du et al, 2011). Some authors emphasize that host density is a key parameter determining the prevalence of hosts (Arneberg et al, 1998;Voutilainen et al, 2009). In our study, higher density of S. woodiana was noted in heated lakes (Kraszewski and Zdanowski, 2001;Spyra et al, 2012), but higher prevalence of mussels was observed in fish ponds.…”
Section: Discussionmentioning
confidence: 99%
“…Positive relationships between trematode infections in snails and secondary intermediate hosts (e.g. amphibians) and the density and species richness of snails have been documented in mesocosm experiments and field studies of standing waters (Johnson et al, 2007;Rohr et al, 2008;Voutilainen et al, 2009). However, other studies have shown that the abundance of vertebrate definitive hosts (e.g.…”
Section: Introductionmentioning
confidence: 99%